Transparancy and Accountability Contribution Toward Sustainability of Banking Sector in Indonesia - Helma Malini (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
ABSTRACT- The board of directors, administrators, and top management personnel all play a role in establishing strategies, setting goals, and assigning duties to implementers. One of the primary goals of corporate governance is to increase shareholder value. On this basis, it can be argued that corporate governance is a critical component of any business's long-term viability. The goal of the study was to see how transparency and accountability affected the banking sector's long-term viability. The study was guided by three theories: agency theory, stewardship theory, and stakeholder’s theory, all of which provide important information on corporate governance processes and how different stakeholders' interests are addressed. This study employs a quantitative research methodology. It is used to quantify a problem in quantitative research by generating numerical data or data that can be turned into useable statistics. Transparency, accountability, justice, and responsibility, according to the study, all have a substantial impact on the banking industry's long-term viability. The study suggests that transparency and accountability have a favorable and considerable impact on the banking industry's long-term viability. The result suggesting that all Indonesian banks' management should strictly enforce openness in all operations and activities conducted by workers in order to achieve sustainability.